2003
DOI: 10.1002/ddr.10212
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of A2B adenosine receptors in the U87MG tumor cells

Abstract: Adenosine is released in increased amounts during hypoxic conditions and is a potential mediator of angiogenesis. The aims of this study were to determine the effect of adenosine on the release of angiogenic factors from the glioblastoma cell line U87MG and the subtypes of adenosine receptors that mediate this effect of adenosine. The adenosine analog NECA increased the release of IL-8 to 160713% of control at 24 h. As a positive control, cobalt (100 mM), a metal ion capable of inducing hypoxia-like effects, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…Furthermore, our results indicate that, in tumor colon hypoxic cells, adenosine increases VEGF promoter activity via the HIF-1 pathway and that caffeine is able to block this effect. It has been reported, in previous studies, that A 2B receptors stimulate IL-8 production in normoxic conditions (Zeng et al, 2003). In this study, we found that also in hypoxia, there is a modulation in IL-8 levels mediated by the adenosine receptor agonist NECA.…”
Section: Discussionsupporting
confidence: 75%
“…Furthermore, our results indicate that, in tumor colon hypoxic cells, adenosine increases VEGF promoter activity via the HIF-1 pathway and that caffeine is able to block this effect. It has been reported, in previous studies, that A 2B receptors stimulate IL-8 production in normoxic conditions (Zeng et al, 2003). In this study, we found that also in hypoxia, there is a modulation in IL-8 levels mediated by the adenosine receptor agonist NECA.…”
Section: Discussionsupporting
confidence: 75%
“…This view has been supported by a large body of evidence provided by pharmacological analysis of adenosinedependent cytokine and growth factor secretion in various cells, tissues, and organs (8,11,13,18,(31)(32)(33)(34)(35)(36)(37)(38). Pharmacological inhibition of A 2B receptors significantly reduced elevations in proinflammatory cytokines as well as mediators of airway remodeling induced by high adenosine levels in the lungs of ADA-deficient mice (8).…”
Section: Discussionmentioning
confidence: 95%
“…In support of this, A 2B AR knockout mice, administered Lewis lung carcinoma, demonstrated reduced tumor growth and survival times (Ryzhov et al, 2008). Studies performed on U87 MG human glioblastoma cells only detected transcripts for A 1 , A 2A and A 2B ARs, but no transcript for A 3 AR (Zeng et al, 2003). However, Merighi et al (2006) were able to detect A 3 AR in these cells.…”
Section: Adenosine Receptors In Cancermentioning
confidence: 80%